2010
DOI: 10.1111/j.1742-1241.2010.02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin: review of preclinical and clinical data regarding incidence of pancreatitis

Abstract: Recent case reports of acute pancreatitis in patients with type 2 diabetes (T2DM) treated with incretin-based therapies have triggered interest regarding the possibility of a mechanism-based association between pancreatitis and glucagon-like peptide-1 mimetics or dipeptidyl peptidase-4 (DPP-4) inhibitors. The objective of this review was to describe the controlled preclinical and clinical trial data regarding the incidence of pancreatitis with sitagliptin, the first DPP-4 inhibitor approved for use in patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 31 publications
6
88
1
3
Order By: Relevance
“…In this pooled analysis, in which 82% of patients had cardiovascular risk factors in addition to diabetes and CVD, there was no difference between groups in the evaluation of cardiovascular complications overall, but a trend for a lower incidence of major ischemic events in the sitagliptin-treated group than in the non-exposed group, as already mentioned [63]. Finally, the same pooled analysis of controlled clinical trials revealed similar incidence rates of pancreatitis in patients treated with sitagliptin compared with those not treated with sitagliptin (0.08 events per 100 patientyears vs 0.10 events per 100 patient-years, respectively) [70]. Nevertheless, post-marketing careful check of the incidence of pancreatitis with incretin-based therapies, including sitagliptin, is still recommended.…”
Section: Sitagliptinsupporting
confidence: 57%
“…In this pooled analysis, in which 82% of patients had cardiovascular risk factors in addition to diabetes and CVD, there was no difference between groups in the evaluation of cardiovascular complications overall, but a trend for a lower incidence of major ischemic events in the sitagliptin-treated group than in the non-exposed group, as already mentioned [63]. Finally, the same pooled analysis of controlled clinical trials revealed similar incidence rates of pancreatitis in patients treated with sitagliptin compared with those not treated with sitagliptin (0.08 events per 100 patientyears vs 0.10 events per 100 patient-years, respectively) [70]. Nevertheless, post-marketing careful check of the incidence of pancreatitis with incretin-based therapies, including sitagliptin, is still recommended.…”
Section: Sitagliptinsupporting
confidence: 57%
“…These concerns include possible triggers for acute pancreatitis and initiation or acceleration of histological changes, suggesting silent or clinical chronic pancreatitis with preneoplastic lesions and potentially pancreatic cancer (2,3). Although some reports have supported the linkage of type 2 diabetes treatment with dipeptidyl peptidase-4 (DPP-4) inhibitors or GLP-1 receptor agonists and increased risk of pancreatitis (4,5), others have not supported this association (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…In a human autopsy series, use of incretin-based therapies was associated with an increase in whole pancreas cell proliferation and presence of PanIN (Butler et al 2013a); however, a variety of methodological issues, such as differences between the studied groups with respect to age, gender, disease duration, and treatments, limit the ability to interpret this study (Drucker 2013;Kahn 2013;BonnerWeir, In't Veld, and Weir 2014). In contrast to studies suggesting a relationship between incretin therapy and proliferation of the exocrine pancreas, toxicology studies using liraglutide (Nyborg et al 2012;Gotfredsen et al 2014), exenatide (Tatarkiewicz et al 2010), lixisenatide (European Public Assessment Report, Lyxumia [EPAR] 2012), albiglutide (Mirabile, Kambara, and Maier 2013), semaglutide (Gotfredsen et al 2014), and sitagliptin (Engel et al 2010) did not detect proliferative lesions in the pancreas due to treatment nor were pancreatic tumors increased in rodent carcinogenicity studies. These studies included evaluation of pancreatic histology in mice, rats, dogs, and monkeys in toxicology studies that utilized relatively high doses of these agents.…”
Section: Discussionmentioning
confidence: 99%